Fingerprint recognition using morphological image processing - Faradila, Rahmatan (2009)
Fingerprint recognition using Morphological image processing method in fingerprint identification: The first approach, which is fingerprint pre-processing were includes filtering, enhancement, binarization and thinning image using morphological image processing method. And the second approach, which is uses histogram matching fingerprint for the output fingerprint result. Current fingerprint recognition systems are that they require a large amount of computational resources, especially when operating in the identification mode. For limiting the costs of identification case and make the result for identification by using morphological method very smooth and accuracy. Fingerprint image enhancement is to make the image clearer for easy further operations. So, this project using morphological image processing to enhance the fingerprint image and using histogram matching method for the output. The project is developed using Matrix Laboratory (MATLAB) programming.